Unraveling the nexus: Socioeconomic and environmental determinants of chronic diseases and health challenges in Saudi Arabia - Khan, Sania (International Journal of Innovative Research and Scientific Studies, 2025)
Saudi Arabia is facing substantial public health challenges, especially in its urban areas, where chronic diseases like diabetes, cardiovascular diseases, and obesity are becoming more prevalent. This research investigates the intricate relationships between socioeconomic and environmental factors that contribute to these health issues and influence the evolution of health policies in the country. Data were collected from 348 urban Saudi citizens to analyze the impact of these factors on the rising rates of chronic diseases. Using quantitative analysis with SPSS and structural equation modeling (AMOS), the research aimed to identify the key drivers of health disparities and evaluate how these factors are currently addressed in public health policy. The study identified climate change and extreme weather, as well as a lack of greenery, as key predictors of chronic disease prevalence, followed by hereditary and genetic factors. Enhancing health education, promoting cultural and social norm shifts, and developing sustainable urban infrastructure could significantly contribute to reducing chronic diseases. Furthermore, the study assessed the effectiveness of existing health policies and provided recommendations for sustainable and integrated strategies to reduce health risks. The findings offer crucial insights for developing more equitable health systems, ultimately improving health outcomes for diverse populations across Saudi Arabia. This supports the enhancement of healthcare quality in line with Saudi Vision 2030 and aligns with Sustainable Development Goal 3 (SDG 3).